2007
DOI: 10.1590/s1517-83822007000400024
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of medicinal plant extracts

Abstract: The present study aimed at evaluating the in vitro antimicrobial activity of methanolic extracts of some medicinal plants against Escherichia coli, Salmonella Typhimurium, Staphylococcus aureus and Enterococcus sp. The methanolic extract of Caryophyllus aromaticus presented the highest anti-S. aureus activity and was effective against all bacterial strains tested. 3815-3744. E-mail: ary@ibb.unesp.br Further acquaintance with different ethnic groups has contributed to the development of research on natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 7 publications
1
53
0
8
Order By: Relevance
“…Mitidiero (2002) demonstrou que esta terapia alternativa permite manter a sanidade do rebanho em padrões semelhantes aos da alopatia, constituindo-se assim, em uma opção viável para os produtores de leite. Estudos in vitro visando à determinação do potencial antimicrobiano de plantas pertencentes à flora brasileira têm demonstrando resultados satisfatórios (Granato et al 2005, Oliveira et al 2007, Ushimaru et al 2007), porém observase a descontinuidade destes estudos e uma fragmentação dos resultados, não permitindo muitos avanços na área.…”
Section: Estratégias De Controle E Prevençãounclassified
“…Mitidiero (2002) demonstrou que esta terapia alternativa permite manter a sanidade do rebanho em padrões semelhantes aos da alopatia, constituindo-se assim, em uma opção viável para os produtores de leite. Estudos in vitro visando à determinação do potencial antimicrobiano de plantas pertencentes à flora brasileira têm demonstrando resultados satisfatórios (Granato et al 2005, Oliveira et al 2007, Ushimaru et al 2007), porém observase a descontinuidade destes estudos e uma fragmentação dos resultados, não permitindo muitos avanços na área.…”
Section: Estratégias De Controle E Prevençãounclassified
“…2005; Ushimaru et al, 2007;Viegas et al, 2000;Miranda et al, 2013 (Moreira et al, 2014). Outra bactéria foco deste trabalho é pertencente ao gênero Bacteroides, à espécie B. fragilis avaliada apesar de minoritária na microbiota intestinal, é a mais frequentemente associada a processos infecciosos, tais como bacteremias, infecções intra-abdominais, abscessos e infecções em tecidos moles (Nakano et al, 2004).…”
Section: Introductionunclassified
“…The MIC value for garlic in the mentioned study was found as 4.48 mg/ml for Enterococcus strains. Grampositive bacteria were more susceptible to extracts of cloves and Indian hyacinth (24).…”
Section: Discussionmentioning
confidence: 99%